No More Silence : An Oral History of the Assassination of President Kennedy - Sneed, Larry A. (Book collections on Project MUSE., 1998)
The work points to the question; was there a conspiracy in the assassination of President Kennedy? It aims to give readers a good perspective on the subject, allowing them to sift through the evidence and draw their own conclusions.